An Intron Variant of SLC2A9 Increases the Risk for Type 2 Diabetes Mellitus Complicated with Hyperuricemia in Chinese Male Population - Xuan-Long YI; Jiang LI; Dong-Mei MENG; Yan-Jun LIU; Yan-Hong LIU; Hong-Min MA; Ying YUAN; Shi-Chao XING (Tehran University of Medical Sciences, 2018)
Background: The aim of this study was to explore the associations of haplotypes of the glucose transporter 9 (SLC2A9) genes with type 2 diabetes mellitus (T2DM) complicated with hyperuricemia (HUA). Methods: Overall, 608 Chinese males, enrolled from the Affiliated Hospital of Medical College of Qingdao University in 2009-2012, were genotyped. The subjects included 167 withT2DM (average age of onset (58.07±11.82 yr), 198 with HUA subjects (average age of onset (39.20±9.73) yr), 115 with T2DM complicated with HUA (average age of onset (51.24±10.09) yr), and 128 control subjects (average age (41.92±10.01) yr). Patients genotypes of the SNPs; including rs734553 was determined by PCR method. Each genotype was regressed assuming the co-dominant, dominant and the recessive models of inheritance with covariates of duration of total glucose, uric acid, urea nitrogen, triglyceride, cholesterol, and creatinine levels. Results: Chi-square test revealed that rs734553polymorphism was both significantly associated with HUA as well as T2DM complicated HUA, but not with pure T2DM. After adjustment for age and gender, analysis showed that people with C allele had higher risk of HUA andT2DMcomplicated HUA than those without C allele. And none of the subjects had the homozygous genotype for SLC2A9 (CC). Conclusion: The SLC2A9 mutation increases the risk for T2DM complicated HUA in Chinese population, which suggested that intron variants between two relatively conserved exons could also be associated with diseases. In patients of T2DM complicated with HUA, the diagnosis and detection of SLC2A9 gene variants should be caused enough attention.